New perspectives on teaching and learning modern languages - Green, Simon (Modern languages in practice, 2000)
This publication examines research-based analysis, structural contexts and classroom practice in teaching and learning. After analyzing the current situation, each contributor proposes radical solutions to current problems and the whole book provides thinking on methodology and pedagogy.